Development of Eco-efficient bricks – A Life Cycle Assessment Approach - Zhang, Xihong; Biswas, Wahidul (ELSEVIER, 2021)
This paper presents the results of techno-economic and environmental performance of interlocking and conventional bricks used for building wall production. Techno eco-efficiency framework consisting of compressive strength test and tensile strength derivation for structural performance assessment and life cycle assessment for determining eco-efficiency performance was applied to determine the Eco-efficient bricks. The replacement of conventional plain bricks with interlocking blocks improved the structural mechanical performance. This construction strategy could substantially reduce construction time, minimize labour cost, and increase mechanical performance. The techno-eco-efficiency framework determined that four out of five interlocking bricks using PT tendon, rebar and mortar could deliver the required level of compressive and tensile strengths with reduced level of environmental impacts in a cost competitive manner. These interlocking bricks are thus known as ‘Eco-efficient’ bricks. However, the conventional bricks are not completely eco-efficient mainly due to higher environmental impacts than the interlocking bricks and they were only found to be eco-efficient in terms of tensile strengths.